2019
DOI: 10.1158/1538-7445.sabcs18-gs1-10
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS1-10: Phase III study of trastuzumab emtansine (T-DM1) vs trastuzumab as adjuvant therapy in patients with HER2-positive early breast cancer with residual invasive disease after neoadjuvant chemotherapy and HER2-targeted therapy including trastuzumab: Primary results from KATHERINE

Abstract: Background: Patients with HER2-positive early breast cancer who have residual invasive disease after neoadjuvant chemotherapy plus HER2-targeted therapy have a high risk of recurrence and death. The current standard of care is continuation of the same HER2-targeted therapy in the adjuvant setting for one year. T-DM1 has shown activity and a favorable benefit-risk profile in metastatic patients with disease progression after prior chemotherapy plus HER2-targeted therapy. Thus, T-DM1 may also be active in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
10
0
4
Order By: Relevance
“…In this context, HER2 3+ tumors have been reported to benefit more from T-DM1 than other IHC groups in retrospective and prospective studies [ 7 , 18 ]. Moreover, benefit associated with the use of post-neoadjuvant T-DM1 as compared to trastuzumab in the KATHERINE trial appeared to more marked in HER2 3+ than in HER2 2+ tumors [ 19 ]. Greater benefit to T-DM1 in HER2 3+ tumors has also been reported in the KATE2 trial [ 20 ] and other cancer types [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, HER2 3+ tumors have been reported to benefit more from T-DM1 than other IHC groups in retrospective and prospective studies [ 7 , 18 ]. Moreover, benefit associated with the use of post-neoadjuvant T-DM1 as compared to trastuzumab in the KATHERINE trial appeared to more marked in HER2 3+ than in HER2 2+ tumors [ 19 ]. Greater benefit to T-DM1 in HER2 3+ tumors has also been reported in the KATE2 trial [ 20 ] and other cancer types [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phase III CREATE X study showed for the first time that, by adapting the postoperative therapy to the pathological response to the neoadjuvant therapy, the risk of recurrence and mortality can be significantly decreased 67 . While the CREATE X study included only patients with a HER2-negative breast cancer who did not achieve pCR through neoadjuvant chemotherapy, the KATHERINE study tested the same approach in patients with HER2-positive breast cancer 103 , 104 . This study included 1486 patients with primary HER2-positive breast cancer who had not achieved pCR following neoadjuvant standard therapy with at least one taxane and trastuzumab for at least 9 weeks.…”
Section: Therapy Of Primary Her2-positive Breast Cancermentioning
confidence: 99%
“… Invasive disease-free survival when comparing the two randomisation arms of the Katherine study (modified according to 104 ). …”
Section: Therapy Of Primary Her2-positive Breast Cancermentioning
confidence: 99%
“…▶ Fig. 4 Invasive disease-free survival when comparing the two randomisation arms of the Katherine study (modified according to [104]).…”
Section: Discussionmentioning
confidence: 99%
“…The phase III CREATE X study showed for the first time that, by adapting the postoperative therapy to the pathological response to the neoadjuvant therapy, the risk of recurrence and mortality can be significantly decreased [67]. While the CREATE X study included only patients with a HER2-negative breast cancer who did not achieve pCR through neoadjuvant chemotherapy, the KA-THERINE study tested the same approach in patients with HER2positive breast cancer [103,104]. This study included 1486 patients with primary HER2-positive breast cancer who had not achieved pCR following neoadjuvant standard therapy with at least one taxane and trastuzumab for at least 9 weeks.…”
Section: Improvement In Prognosis Through a Switch To T-dm1 In The Camentioning
confidence: 99%